Preliminary Efficacy and Feasibility of "Thinking While Moving in English": A Program with Physical Activity Integrated into Primary School English Lessons - Myrto F. Mavilidi; David R. Lubans; Narelle Eather; Philip J. Morgan; Nicholas Riley (MDPI AG, 2018)
Background: The physical, cognitive, and learning benefits of physical activity for children have already been established. However, many schools are failing to provide children with sufficient activity at school due to a crowded school curriculum. Physical activity interventions that integrate physical activity with learning is a way to enhance physical and cognitive benefits without loss of academic time. This study evaluated the preliminary efficacy and feasibility of "Thinking While Moving in English", a primary school program that integrates physical activity into English lessons. Method: Two classes of Grade 4 students (n = 55, 10-11 years old) were randomly assigned to the intervention (n = 29) or control (n = 26) conditions. The program components consisted of 3 × 40 min physically active academic lessons per week, delivered over a 4-week period. The following measures were taken at baseline and immediate post-intervention: on-task behavior, cognition (inhibition and working memory), and learning outcomes (spelling and grammar). Results: Results revealed significant improvements in on-task behavior and spelling in the intervention group, compared to the control group. There were no observed improvements in cognitive outcomes or grammar. Conclusions: This study provides preliminary evidence for the efficacy of physically active English lessons to enhance children's educational outcomes.